KEHIDUPAN SETELAH KEMATIAN DALAM PERJANJIAN LAMA DAN KEYAKINAN BATAK TOBA - Grecetinovitria Merliana Butar-butar (Institut Agama Kristen Negeri Tarutung, 2019)
AbstractThe entry of Christianity into the Batak land made a shift in the belief value of the Batak Toba people. This paper discusses beliefs about human spirit life after death in the Old Testament and in the beliefs of pre-Christian Batak people.The Israelites believed in a life form after death, death is not annihilation, but the transition to another type of existence in sheol. BatakToba people believe that there is life after death even more have power. In addition to the mention of begu, sumangot and sahala, in the Toba Batak community, people who have died arealso called tondi.Keywords: Life, After Death, Old Testament, Toba Batak Beliefs